Instructional Design for Student Learning on Quantum Tunneling - Lamichhane, Shova Kanta (Himalayan Physics, 2012)
Acquiring mathematical, conceptual, and problem-solving skill is required in university-level physics courses. Average students often lack the knowledge and study skills need to succeed in physics, preciously in quantum physics course. The reasons for these difficulties are more subtle and some of them are brought to the surface. Addressing how to build models of wave functions and energy and how to relate these models to real physical systems is a challenging job. Article has opened up a floodgate of deep and difficult task for students struggle to make sense of these models. Article has discuss the difficulties and the real issues of student in learning quantum tunneling to build the models that are implicit in experts’ understanding. So that, in addition to class attendance and/or group study, students must also learn to work by themselves to develop the mathematical, conceptual, and problem-solving skills they need. The Himalayan Physics Vol. 3, No. 3 2012 Page : 27-34